STRATEGI PENGELOLAAN DESA PANCASARI, KECAMATAN SUKASADA,KABUPATEN BULELENG SEBAGAI KAWASAN DAYA TARIK WISATA KHUSUS - Septiani Utami, Ida Ayu Kade (Jurnal Ilmiah Pariwisata, 2012)
Pancasari village having beautifully natural potency with its uniqueness has been determined by the government as Kawasan Daya Tarik Wisata Khusus (KDTWK). KDTWK is a concept of developing a tourism destination for the conserving purpose. In fact, however, the management of the destination is still inadequate. It can be seen trough the problems faced in executing tourism activities in that village. It is, therefore required to review the potencies owned by such tourism destination. It consist of how the involvement of all stakeholders and determine appropriate strategies to develop the tourism object based on the concept to achieve the aims of KDTWK. In order to answer the above problem, a qualitative research and simple SWOT analysis were applied in this research, such as observation, interview and library analysis. An observation sheet was used to record everything observed by the researcher and interview guides were produced to find the answer of all problems. Physical poten cies owned by Pancasari village are including lake, village atmosphere, gardening, farming and forest. Non physical ones are among others : the villagers with their ways of life and custom, as well as the culture that are still maintained in their lives. The involvement of stakeholders, still needs to be well coordinated. It can be seen from the negative phenomenon happened during the tourism activities.
Keywords: strategy, potency, management